Banking Service and Customer Satisfaction in Commercial Banks: Nepalese Perspective - Singh, Hridayaswor Bir (Rural Development Journal, 2019)
The banking sector has become competitive significantly like other service-oriented businesses. Banks are continuously looking for ways to enhance their service and trying to distinguish themselves from competitors. As the quality of service has attracted the major attention of bankers over the recent years understanding its role in customer satisfaction, this study focused on this aspect. Bank is financial intermediary accepting deposits and granting loans (Singh H. B, 2005). It offers the widest menu of financial services to its customers (Singh, 2005). In the contemporary context, the Nepalese banking industry has played a significant role in the development of the economy. Banks of Nepal have adopted liberal policy and have established a strong foundation through quality services (Gautam, 2016). The growing competition in the banking sector has made it essential for bank management to understand customers’ wishes regarding the service quality offered by banks to enhance customer satisfaction and optimize the profitability of banks. In this regard, this study explores to answer the following question; what are the customers’ views and demand on the banking service offered by commercial banks in Nepal? The study identified the possible expectations that customers have on the quality of banking service. The study adopted a descriptive design with population of interested customers of commercial banks in Kathmandu, the capital of Nepal. Questionnaires were administered to customers from a total of 28 commercial banks located within Kathmandu valley. The findings from the study established a positive relationship between service quality and customer satisfaction in Nepalese commercial banks. The conclusion from this study is that customer satisfaction can lead to customer retention in commercial banks. Recommendations based on the findings will help to enhance the satisfaction and retention of customers if they are implemented in the Nepalese banks.